Assessment of nano-particles for the removal of bacteria and viruses from aquatic systems - Tejesh, Kukatla; M, Dr. Thiru Chitrambalam; Y, Dr. Swarna Latha; Pattanaik, Dr. Bramhadev; S.K, Dr. Manju Bargavi; Kushwaha, Dr. Ravikant; Dev, Anoop (International Journal of Aquatic Research and Environmental Studies, 2025)
Utilising a designed material or finished product with at least one dimension between 1 and 100 nm is the foundation of nanotechnology’s enabling power. In addition to their size and optical characteristics, nanomaterials also differ from bulk materials in terms of their composition, shape, surface layer, reactivity, and toxicity, among other physical and chemical characteristics. With over 1800 nanoproducts currently available on the market, nanotechnology is expected to transform product development and manufacturing, potentially generating up to three trillion US dollars in global economic output by 2020. Direct exposure and its effects on certain aquatic creatures are the main topics of studies on the safety of nanomaterials in aquatic environments. Little is known about how nanomaterials interact with biotic and abiotic elements and how this affects creatures in the food web at the cellular and molecular level. The interaction and impacts of the most common metal nanoparticles in the aquatic environment have been examined in this paper. To harness the power of this enabling technology, nanotechnology, "safe by design" nanomaterials will be developed as a result of the current work’s understanding of the eco-bio-compatibility of these novel materials.